Resistant and susceptible rainbow trout (Oncorhynchus mykiss) lines show distinctive immune response to Lactococcus garvieae. Issue 105 (October 2020) - Bulfon, Chiara; Prearo, Marino; Volpatti, Donatella; Byadgi, Omkar; Righetti, Marzia; Maniaci, Maria Grazia; Campia, Valentina; Pastorino, Paolo; Pascoli, Francesco; Toffan, Anna; Biolatti, Cristina; Acutis, Pier Luigi; et al.
Abstract: Lactococcosis is one of the main bacterial diseases affecting rainbow trout ( Oncorhynchus mykiss ), with significant economic and sanitary repercussion. Vaccination and antibiotic treatments are commonly used to prevent and control the infection outbreaks; however, these strategies have some drawbacks including limited coverage, handling costs, induction of antibiotic resistance and chemical residues in the environment. Selective breeding programs represent a promising complementary approach for increasing fish disease resistance in commercial farms and some immunological parameters may be tentatively used as indirect indicators for this purpose. The present study investigated for the first time some innate and adaptive immune responses in two groups of rainbow trout derived from selected lines (susceptible and resistant) showing a different "in field" phenotypical resistance to Yersinia ruckeri, Flavobacterium branchiophilum, F. psychrophilum, and Ichthyophthirius multifiliis, after an immersion-dilution based exposure to Lactococcus garvieae carried out in controlled experimental conditions. Twenty-six resistant and twenty-six susceptible female rainbow trout (mean body weight 80 g, 9 months aged, F5 generation) were obtained from an intensive farm considered L. garvieae free and were exposed to the pathogen. Moreover, 10 resistant and 10 susceptible fish were used as uninfected controls. After 5 days, blood and tissue samples were collected for immunological analyses. A significantly higher serum and mucus lysozyme activity was recorded in resistant rainbow trout compared to susceptible fish ( P ≤ 0.05), both before and after exposure to L. garvieae . Similarly, respiratory burst activity of head kidney leukocytes resulted more intense in resistant fish ( P ≤ 0.05), suggesting that phagocytes could more quickly activate their microbicidal mechanisms to counteract the bacterial spread. Resistant group displayed also an up-regulation of immunoglobulins M (IgM), major histocompatibility complex II (MHC-II) and interleukin 8 (IL-8) gene expression ( P ≤ 0.05) and a significantly higher blood lymphocytes count ( P ≤ 0.05), highlighting their potential better ability to trigger the recruitment of defensive cells and the initiation of specific immune processes such as antigen presentation to CD4 + T lymphocytes and IgM synthesis. The results herein presented might be useful for the identification of immunological markers to be used as indirect indicators in rainbow trout selective breeding programs. Highlights: Selected rainbow trout lines exhibited different attitude to control lactococcosis. Resistant fish showed higher lysozyme activity to resist L. garvieae infection. Resistant fish more effectively trigger specific immune response against L. garvieae .